A Transitivity Analysis of Discourses in George W. Bush and Scott Morrison’s Speeches on ‘War on Terror’ - Irma Suryani; Sawirman (Andalas International Journal of Socio-Humanities, 2021)
This article is a continuation of the article entitled Comparing Discourses in George W. Bush and Scott Morrison’s Speeches on ‘war on terror’ about the transitivity systems, including types of processes, participant functions, and circumstance elements, are used in these two speech discourses by George W. Bush and Scott Morrison. This research is qualitative research with a descriptive statistical method that presents linguistic analysis findings in speech discourses about the war on terror. This article aims to identify and explain how George W. Bush and Scott Morrison construct the image of terrorism through the language used in their speech discourses. The analysis uses Systemic Functional Linguistics (SFL) and utilizes the framework of transitivity analysis, which identifies the ideational meaning embodied by choice of grammar. This study found that George W. Bush uses material processing to show a negative image of terrorism. In addition to the material process, Scott Morrison also uses a verbal process to convey the image of terrorists. The linguistic features in both speech discourses both depict a negative image of terrorists. The findings also prove that the choice of grammar in the two discourses indirectly uses the speaker’s perspective on terrorists, which influences listeners' opinion.